EFFECT OF IRRIGATION WITH PRE-HEATED AND ULTRASONICALLY ACTIVATED SODIUM HYPOCHLORITE AT DIFFERENT CONCENTRATIONS ON POSTOPERATIVE PAIN LEVEL: A RANDOMIZED CONTROLLED CLINICAL STUDY (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Pain relief and complete disinfection is the primary goal of root canal treatment in any tooth. Post Operative pain is multifactorial and one of the factors affecting it is sodium hypochlorite used as an irrigant. Aim: The aim of the present study is to evaluate the effect of pre-heated and ultrasonically activated sodium hypochlorite on post operative pain when used at different concentrations. Materials and Methods: In this randomized control trial, 80 patients were evaluated and divided into 4 groups. Two concentrations of NaOCl were used at 3% and 5.25%. For each concentration, preheated solution and ultrasonic activation is used. All treatments were done in single session on mandibular molars. Presence of post-operative pain was calculated at 6h, 24h, 48h, 72h on VAS scale. Pre-operative pain was also considered. Data regarding the intensity of postoperative pain was analysed for normality using one-way Anova. Results: Overall, mean postoperative pain intensity was low, with the majority of patients having no or minimal pain 72 hours postoperatively. Comparison of pain postoperatively after 6 hours shows that the amean value of Group 2(5.25% pre-heated NaOCl) (2.9) is highest followed by Group 4(2.2), Group 1(2.05) least in Group 3(1.5) (3% UAI-NaOCl)Conclusion: Pre-heated and ultrasonically activated irrigation resulted in low and comparable levels of postoperative pain. Pre-heated 5.25% NaOCl was associated with higher amount of pain comparatively. Though Post-operative pain overall from all the groups yielded similar results, using low concentration NAOCL and UAI is a more suitable option.